Psychometric properties of the Persian version of the just culture questionnaire (JCQ) - Yahya Rasoulzadeh (Salāmat-i kār-i Īrān, 2017)
Background and aims: Just culture is conceptualized as a rational approach to human error and its fallibility. A good evaluation of just culture in an organization is needed to effectively design and implement of preventive measures to reduce the events and injuries. This study aimed to evaluate the psychometric features of the Persian language version of just culture questionnaire (JCQ).